2003
DOI: 10.2527/2003.81123035x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ecological analysis of porcine ileal microbiota responses to antimicrobial growth promoters1

Abstract: Cultivation-independent microbial molecular ecology approaches were used to examine the effects of antibiotic growth promoters on the pig ileal microbiota. Five-week-old barrows were fitted with a simple T-cannula at the distal ileum. Three diets meeting or exceeding the minimum nutrient requirements were fed for 5 wk and supplemented as follows: 1) negative control (no antibiotic; n = 5), 2) continuous tylosin administration (n = 5), and 3) an antibiotic rotation sequence (wk 1, chlorotetracycline sulfathiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 39 publications
8
91
0
5
Order By: Relevance
“…In previous studies using pigs as an animal model, certain species of Lactobacillus have been shown to increase in concentration in AGP-treated pigs (11,12,20). In this study we also detected a relative increase in the concentration of the genus Lactobacillus.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In previous studies using pigs as an animal model, certain species of Lactobacillus have been shown to increase in concentration in AGP-treated pigs (11,12,20). In this study we also detected a relative increase in the concentration of the genus Lactobacillus.…”
Section: Discussionsupporting
confidence: 71%
“…In comparing the results reported here with those from other studies using AGPs, differences in the microbial population shifts did occur (11,12,20). It is unclear why these differences occurred, but is likely related to differences in the AGP used.…”
Section: Discussionsupporting
confidence: 48%
“…One mechanism that may explain this improved performance is an increase in the relative mass of lactobacilli in the intestinal tract when compared to enterogenic bacteria, owing to a significant decrease of the latter (COLLIER et al, 2003;BOSI et al, 2011). Therefore, because of the prevalence of lactobacilli within the small intestine, where the majority of nutrient absorption occurs, the alteration of these bacteria is a potentially important mechanism involved in antibioticinfluenced animal growth (COLLIER et al, 2003). Macrolides are known to be minimally effective against Gram-negative bacteria in the intestine because of the outer membrane permeability barrier of Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous studies demonstrating a beneficial effect of feeding pigs Lactobacillus species (Cho et al 1992;Abe et al 1995;Tortuero et al 1995;Bomba et al 1998;Ragland and Adeola 2002) and Bacillus species (Bonomi 1992;Vassalo et al 1997;Zani et al 1998;Adami and Cavazzoni 1999;Kyriakis et al 1999), while fewer positive effects have been found using Enterococcus species (Jin et al 2000). In swine, the use of probiotics appears to give more consistent and positive effects in piglets than in grower-finisher pigs (Savage 1977;Cole 1991). Pollman et al (1980) demonstrated improved average daily gain (4.5%) and feed conversion (FC) (7.2%) in starter pigs fed L. acidophilus, compared with control animals receiving no antibiotic or probiotic -results that are consistent with documented benefits of subtherapeutic antibiotics (Doyle 2001).…”
Section: Probioticsmentioning
confidence: 99%
“…Antibiotics added to swine feed in subtherapeutic doses have been reported to improve growth rate (Cromwell 2002;Collier et al 2003). Although the mechanisms involved with the growth-promoting effects of antibiotics are not clearly understood, it has been postulated that they increase growth rate as a result of improved gut health, nutrient utilization and improved feed conversion efficiency (Visek 1978).…”
Section: Antibiotic Resistance and The Use Of Subtherapeutic Antibiotmentioning
confidence: 99%